Modelamiento termodinámico de la obtención de carbonato de glicerol a partir del glicerol (2024)
"Since glycerol production exceeds demand, it is of great use and interest to investigate the feasibility of using it as a raw material in obtaining different substances, providing new opportunities for valorization. Among the products that can be obtained with glycerol are glycerol carbonate, glyceraldehyde, glyceryl ether, acetol, propane, 1,2-propanediol, monoacetin, among others. Of these, glycerol carbonate (GC) stands out because it can be used as an input in a wide range of applications, despite this, its commercial value remains high $8/kg in 2014 [1] since its production has been limited. Currently, there are several theses, articles and scientific documents on the synthesis of glycerol carbonate from urea, carbon dioxide, ethylene carbonate or dimethyl carbonate. From the point of view of the environment and sustainability, the most attractive reaction is the one that uses carbon dioxide, in which is the carbonation of glycerol to produce glycerol carbonate (GC). However, there are no thermodynamic studies to support this reaction, hence the value of this project, which aims to provide a deep understanding of the thermodynamic behavior of the glycerol carbonate production reaction. This degree work carried out a thermodynamic modeling of the production of glycerol carbonate from glycerol with Peng-Robinson. By performing the modeling, the enthalpy, entropy and Gibbs energy were estimated at different conditions, where it was observed that it is an exothermic, spontaneous and feasible reaction. This research project does not analyze the chemical equilibrium, reaction progress, conversion and exergy.